Pengaruh Model Pembelajaran Problem Based Learning dengan Menggunakan Asesmen Kinerja Terhadap Hasil Belajar Fisika Siswa Kelas X SMA Negeri 1 Dondo - Syahbudin, Aryani; Darmadi, I Wayan (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2023)
The study applauded for examining the impact of the model learning problem based learning by using performance asesment on the physics of a 1 dondo state high school student. The average percentage of learning based learning problems is 79.03% whose learning ability increases and the average percentage following conventional models is 62.15% whose learning ability increases. Hypothetical testing data analysis using uji-u. Statistical test results have concluded that there is an impact on learning students using the model learning problem based learning using performance asesment on the current x - school and energy class of first year high school students.